2018
DOI: 10.7249/tl144.2
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Effectiveness of Interventions to Reduce Motor Vehicle–Related Injuries and Deaths: Supplement to Tool Documentation

Abstract: Limited Print and Electronic Distribution RightsThis document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…We demonstrated that counties located in states identified in this study serve as clusters and hotspots for fatal crash events during the rush hour after adjusting for environmental and county characteristics. Earlier studies have reported increased crash fatality rates in similar states (Ecola et al, 2018;National Highway Traffic Safety Administration, 2018).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We demonstrated that counties located in states identified in this study serve as clusters and hotspots for fatal crash events during the rush hour after adjusting for environmental and county characteristics. Earlier studies have reported increased crash fatality rates in similar states (Ecola et al, 2018;National Highway Traffic Safety Administration, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Prioritizing intervention by states is not a novel approach to reducing fatal crash injury. There have been reports urging state-specific interventions towards specific risk factors associated with fatal crash events (Ecola et al, 2015; Ecola et al, 2018). Since each state within the U.S. is responsible for enacting policies and implementing crash prevention programs (Ecola et al, 2015), the need for tools that will guide decisions and policymakers on prioritization is needed.…”
Section: Discussionmentioning
confidence: 99%
“…A rich literature confirms the benefits of policies designed to prevent distracted drivingsuch as bans on texting while driving -in terms of preventing fatalities and injuries (Ferdinand et al, 2019;Ferdinand et al, 2015). Such information, in turn, permits calculating the costs and effectiveness of interventions designed to prevent motor vehicle injuries (Ecola et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While the overall number of alcohol‐impaired car crashes has decreased in the past 20 years, the annual number of fatalities and injuries has remained stagnant since 2009 (NHTSA, 2017a). To address this major public health problem, intervention and public health efforts have focused on diminishing the number of alcohol‐drinking drivers (Ecola et al., ; Goodwin et al., ). By comparison, far less attention has been directed to passengers who ride with drinking drivers (RWDD).…”
Section: Decision‐making Processes Of Rwddmentioning
confidence: 99%